Communication Conflicts in Family Relationship: A Conversation Analysis of Mother-Daughter Mediation - Duan, Yi Ran; Li, Yang; Wu, Ying Qi (Journal of Pragmatics Research, 2025)
Family is the basic unit of society, and communication conflicts among family members have a great influence on their psychological state and the relationship of the entire family. The parent-child relationship, in particular, often faces tensions arising from communicative differences and misunderstandings. Drawing on Conversation Analysis, this critical case study aims to explore how impoliteness is realized through speech acts in family conflicts between a mother and daughter participating in a mediation show ‘金牌调解’ (Jin Pai Tiao Jie). Findings reveal that high-frequency speech acts like insult and sarcasm significantly escalate mother-daughter tensions, while low-frequency but high-impact acts (e.g., threat and criticism) further damage their relationship; moreover, avoidant speech acts, such as disassociation, fail to resolve conflicts and instead mask deep-seated issues, exacerbating the discord. This study advances the under-researched field of family communication by showing how impoliteness escalates conflicts. This study contributes to offering practical insights for parents and children to recognize and mitigate harmful interactions in daily communication.